TEACHING WORLD CITIES IN ENGLISH: METHODS AND STRATEGIES - Samijonova Gulzira Esonboy qizi; Jololdinov Asror Toshtemirovich (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Annotation: This article explores effective methods and strategies for teaching the topic of "World Cities" in English. It highlights the importance of integrating language skills with geographical and cultural knowledge, suggests engaging classroom activities, and provides recommendations for educators. The article also discusses the use of technology, project-based learning, and interactive discussions to enhance students’ understanding of global urban centers.